Usage of healthcare services and preference for mental healthcare among older Somali immigrants in Finland. Issue 6 (18th August 2019) - Mölsä, Mulki; Tiilikainen, Marja; Punamäki, Raija-Leena
ABSTRACT: Objectives: The aims of the study were, first, to describe and analyze healthcare services utilization patterns of older immigrants in Finland, and particularly to compare the availability and accessibility of health services between older Somalis and Finns. The second aim was to examine the preferences for mental healthcare within the group of Somalis. The third aim was to test the existence of a service usage gap expected to be characteristic of the Somali group, in which high levels of mental health problems occur alongside simultaneous low levels of mental health service usage. Design: The participants were 256 men and women between the ages of 50–85; half were Somali migrants and the other half Finnish matched pairs. The participants were surveyed regarding their usage of somatic, mental, and preventive health services, as well as symptoms of depression, general distress, and somatization. The Somali participants were also surveyed regarding their usage of traditional healing methods and preferences for mental healthcare. Results: The Somali group had significantly lower access to personal/family doctors at healthcare centers as well as a lower availability of private doctors and occupational health services than the Finns. Instead, they used more nursing services than Finnish patients. The Somali participants attended fewer age-salient preventive check-ups than the Finns. The majority of the Somalis preferred traditional care, most commonly religious healing, for mental health problems. The hypothesized service gap was not substantiated, as a high level of depressive symptoms was not associated with a low usage of health services among the Somalis, but it was found unexpectedly among the Finns. Conclusion: Our findings call for culturally appropriate general and mental health services for older immigrants, which requires awareness of clients' preferences, needs, and alternative healing practices. Somali participants encountered institutional barriers in accessing healthcare, and they preferred informal mental healthcare, especially religious healing instead of Western practices.